FORME CURENTE ALE INSTRUIRII ASISTATE DE CALCULATOR ÎN ÎNVĂŢĂMÂNTUL SUPERIOR - USM ADMIN (Moldova State University, 2011)
In this article there are presented some ideas regarding utilization of Computer Assisted Instruction by means of different types of educational software. The main goals of the educational software are to improve the learning activities and offer real possibilities of individualization and informatization of education.